Han, B.-C. (2014). A sociedade do cansaço. Lisboa: Relógio d’Água - Diogo Silva da Cunha (Comunicação e Sociedade, 2015)
The Burnout Society is a translation by Gilda Lopes Encarnação of the German book Müdigkeitsgesellschaft by Byung-Chul Han...